Land Suitability Analysis for the Development of Bathing Tourism Based on Biophysical and Social Parameters in Kunyi Village, Polewali Mandar Regency - Ali Akbar Tasrif; Nur Adyla Suriadi; Muhammad Alfa Reza; Mahfuzur Rahman Syatar; Hamdan Khatiran (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2026)
Kunyi Village in Anreapi District, Polewali Mandar Regency, has promising potential for natural bathing tourism, particularly in the Patipo and Kampung Rumede areas. This potential is reflected in its rocky river character, relatively clear water, comfortable water temperature, good accessibility, and the availability of basic facilities and community support. This study aims to analyze land suitability for the development of bathing tourism based on biophysical and social parameters in Kunyi Village. The study employed a descriptive quantitative approach supported by qualitative analysis. The analysis used a scoring and weighting method applied to biophysical parameters, namely water depth, current velocity, clarity, temperature, and pH, as well as social parameters including accessibility, supporting facilities, and community perception. The results indicate that the land suitability level ranges from 70% to 88%, which falls into the suitable (S2) to highly suitable (S1) categories. The most supportive parameters are current velocity, temperature, pH, and accessibility. Meanwhile, the main limiting factors are variations in river depth across segments and limited sanitation facility capacity during peak visitation periods. The study concludes that Kunyi Village is feasible to be developed as a bathing tourism destination, provided that zoning, sanitation facilities, safety measures, and community-based management are strengthened to ensure safe and sustainable tourism development.